2020
DOI: 10.1108/ijtc-04-2019-0054
|View full text |Cite
|
Sign up to set email alerts
|

Business events at a spa destination: an insight into senior participant motivation

Abstract: Purpose The purpose of this paper is to examine the motivation of the attendees of the Annual Meeting of the Serbian Association of Seniors. The research aims to segment the senior participants according to their push and pull motivations for attending association meetings, by using cluster analysis to understand the role of destination personality in the segmentation process. Design/methodology/approach The questionnaire, based on a seven-point Likert scale, was distributed among representatives and members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
7
0
2
Order By: Relevance
“…Mair, Lockstone-Binney and Whitelaw (2018) revealed that networking opportunities are one of the motivational factors influencing tourists' decisions to attend or re-attend MICE events. Dimitrovski, Seočanac and Luković (2021) also found the networking factor to be important in the business event context. Moreover, Cassar Whitfield and Chapman (2020) affirmed that networking opportunities are an essential factor in the MICE context.…”
Section: Networking Opportunitiesmentioning
confidence: 95%
See 3 more Smart Citations
“…Mair, Lockstone-Binney and Whitelaw (2018) revealed that networking opportunities are one of the motivational factors influencing tourists' decisions to attend or re-attend MICE events. Dimitrovski, Seočanac and Luković (2021) also found the networking factor to be important in the business event context. Moreover, Cassar Whitfield and Chapman (2020) affirmed that networking opportunities are an essential factor in the MICE context.…”
Section: Networking Opportunitiesmentioning
confidence: 95%
“…Push factors are the intangible or psychological factors intrinsic to event participants that drive them to decide to attend a MICE event. Related studies have indicated the importance of networking and educational opportunities as push motivational factors (Cassar, Whitfield, Chapman, 2020;Dimitrovski, Seočanac, Luković, 2021;Gračan, Barkiđija Sotošek, Torbarina, 2021;Kim, Kim, Oh, 2020;Kim, Lee, Kim, 2012;Lee, Koo, Chung, 2019;Mair, Thompson, 2009;Pavluković, Cimbaljević, 2020;Severt et al, 2007;Yodsuwan, Pathan, Butcher, 2020;Yoo, Chon, 2008;Yoo, Zhao, 2010). The following sections explain these factors in detail.…”
Section: Push Factorsmentioning
confidence: 95%
See 2 more Smart Citations
“…Tourists have a desire to visit a foreign country that has a significant cultural heritage, and, on the other hand, cultural tourism enables the realization of profits and encourages economic development (Filipoviš, 2018). Dimitrovski et al (2019) state that there are two groups of motivational factors of travel. Push-factors include recreational holidays, learning foreign languages, making social contacts with people from other cultures, exploring other countries and improving the level of cultural intelligence.…”
Section: Literature Reviewmentioning
confidence: 99%